2022
DOI: 10.1136/bmjopen-2021-053792
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the impact of trained midwives and upgraded health facilities on institutional delivery rates in Nigeria using a quasi-experimental study design

Abstract: ObjectivesStudies have shown that demand-side interventions, such as conditional cash transfers and vouchers, can increase the proportion of women giving birth in a health facility in low-income and middle-income countries, but there is limited evidence of the effectiveness of supply-side interventions. We evaluated the impact of the Subsidy Reinvestment and Empowerment Programme Maternal and Child Health Project (SURE-P MCH) on rates of institutional delivery and antenatal care.Design, setting and participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In this study, we observed that there was increased risk of maternal mortality in districts which had inadequate number of midwives compared with districts which had adequate number of midwives. It has been documented that availability of skilled midwives at health facilities increases the uptake of institutional deliveries and other maternal health services [ 66 ] and consequently reduce the maternal mortality [ 14 , 67 ]. In contrary to this; lack of skilled personnel for maternal health services increases the risk of maternal deaths.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that there was increased risk of maternal mortality in districts which had inadequate number of midwives compared with districts which had adequate number of midwives. It has been documented that availability of skilled midwives at health facilities increases the uptake of institutional deliveries and other maternal health services [ 66 ] and consequently reduce the maternal mortality [ 14 , 67 ]. In contrary to this; lack of skilled personnel for maternal health services increases the risk of maternal deaths.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that there was increased risk of maternal mortality in districts which had inadequate number of midwives compared with districts which had adequate number of midwives. It has been documented that availability of skilled midwives at health facilities increases the uptake of institutional deliveries and other maternal health services [59] and consequently reduce the maternal mortality [14, 60]. In contrary to this; lack of skilled personnel for maternal health services increases the risk of maternal deaths.…”
Section: Discussionmentioning
confidence: 99%
“…To provide further opportunities to educate pregnant women about their health and that of their children, WHO now recommends a higher frequency of antenatal contacts so that further reductions in perinatal deaths can be achieved [ 27 ]. Although this presents an increased cost to CBMs, antenatal service utilization has helped in the early identification of women at an increased risk of pregnancy and childbirth-related complications and has helped them navigate the anticipated problems through apps among other schemes adopted in the community in Benue State [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the maternal mortality ratio (MMR) in Benue state remains as high as 1,189 per 100,000 population, making the state one of the highest contributors to the national average of 576 deaths per 100,000 [ 10 ]. Increased awareness drives, infrastructural development, and cash rewards to CBMs comprise some of the government’s responses to the burden of MMR in Benue state [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%